Characteristics and outcomes of patients with cancer presenting with acute myocardial infarction. Issue 5 (August 2019) - Itzhaki Ben Zadok, Osnat; Hasdai, David; Gottlieb, Shmuel; Porter, Avital; Beigel, Roy; Shimony, Avi; Cohen, Tal; Shlomo, Nir; Shohat, Tamy; Silverman, Barbara; Kornowski, Ran; Iakobishvili, Zaza
Abstract : Background: Limited data are available regarding the optimal management of patients with cancer in the acute myocardial infarction (AMI) setting. Patients and methods: We studied consecutive patients with AMI included in a national registry (years 2010, 2016) with the diagnosis of past or active malignancy and followed them for 1 year. Results: Our cohort consisted of 2937 cancer-naive patients and 152 patients with cancer, of whom 35% presented with active malignancies. Compared with cancer-naive patients, patients with cancer were older, with female predominance, and presented more often with a history of hypertension and chronic kidney disease ( P <0.001 for all comparisons). The rate of ST-elevation AMI was comparable ( P =0.067). GRACE score more than 140 was more common in the cancer group ( P <0.001). Most patients with cancer were referred to coronary angiography, though less than cancer-naive patients (87 vs. 93%; P =0.004). The rate of percutaneous coronary intervention was similar ( P =0.265). Propensity score matching demonstrated similar rates of in-hospital complications between groups, and no mortality or major cardiac adverse event differences were noted at 30 days. Moreover, short-term mortality was similar between patients with active versus past malignancies, and between patients with solid and nonsolid tumors. However, cancer in patients with AMI was found to predict an increased mortality risk at 1 year by multivariable analysis (hazard ratio=2.52; P <0.001). Conclusion: Patients with cancer and AMI have a more complicated clinical presentation, yet their short-term prognosis is similar to cancer-naive patients. Nevertheless, 1-year outcome is worse. Abstract : Supplemental Digital Content is available in the text.